The entitled ally: authorship, consultation, and the 'right' to stage autistic people's stories. Issue 9 (21st October 2021) - Hadley, Bree; Batch, Morgan; Whelan, Michael
Abstract: Theatre has a long tradition of presenting disabled characters as plot devices to tell someone else's story. A recent production, All in a Row, resulted in heated debate around this issue. This article examines not the play itself, but the conflict between those who objected to the play's representation of autism, and its creators, who defended their choices by citing their disability-adjacent identities and processes of consultation. For critics, the fact that the creators did not take the community's concerns seriously was a source of trauma. This article uses this conflict to draw out lessons about how we might better negotiate the right to tell disability stories and strengthen frameworks to support that negotiation. We propose a decision tree diagram to assist artists in understanding the meaning, role, and most importantly the potential consequences of consultation – up to and including a community saying 'no' to an artist's planned representation. Points of interest: Books, television and plays sometimes represent disabled characters in ways that are not like what disabled people are like in real life. A play called All in a Row has an autistic character played by a puppet, which upset many autistic people and their supporters. Many autistic people and their supporters did not like the puppet or the story, but the creators of the play said that it was okay because of their own experiences with disabled people and because they had asked people about the play. We say that when disabled people are asked about a story that is being written about disabled characters, they should have more power to say 'no' to the story. This may be important even for people who believe their own experience means they can ignore feedback. We've made a diagram to help people decide when they should change the story they're writing.